2021
DOI: 10.3389/fcell.2021.721676
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2B-AS1 Promotes Malignancy as a Novel Prognosis-Related Molecular Marker in the Endometrial Cancer Immune Microenvironment

Abstract: The prognosis of patients with endometrial cancer (EC) is closely associated with immune cell infiltration. Although abnormal long non-coding RNA (lncRNA) expression is also linked to poor prognosis in patients with EC, the function and action mechanism of immune infiltration-related lncRNAs underlying the occurrence and development of EC remains unclear. In this study, we analyzed lncRNA expression using The Cancer Genome Atlas and clinical data and identified six lncRNAs as prognostic markers for EC, all of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
(37 reference statements)
0
11
1
Order By: Relevance
“…CDKN2B-AS1 increased NAP1L1 transcription in HCC cells by adsorbing let-7c-5p, which activates the PI3K/AKT/mTOR activity [ 34 ]. Yang et al observed that CDKN2B-AS1 knockdown inhibited endometrial carcinogenesis both in vivo and in vitro, and the tumor size was smaller in the CDKN2B-AS1 knockdown group than in the nonknockdown group [ 35 ]. The current study found that CDKN2B-AS1 is a potential risk for EC.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2B-AS1 increased NAP1L1 transcription in HCC cells by adsorbing let-7c-5p, which activates the PI3K/AKT/mTOR activity [ 34 ]. Yang et al observed that CDKN2B-AS1 knockdown inhibited endometrial carcinogenesis both in vivo and in vitro, and the tumor size was smaller in the CDKN2B-AS1 knockdown group than in the nonknockdown group [ 35 ]. The current study found that CDKN2B-AS1 is a potential risk for EC.…”
Section: Discussionmentioning
confidence: 99%
“…By combining the results of this experiment with previous related studies [27,31,32], we believe that CDKN2B-AS1 and miR-199a-5p can be used as clinical routine screening indicators, so as to improve the early diagnosis rate of LC and provide relevant treatment for patients in a timely manner. What is more, CDKN2B-AS1 with miR-199a-5p can be used as an indicator of disease progression in LC to aid clinical understanding of disease progression.…”
Section: Discussionmentioning
confidence: 57%
“…AUC of the risk model was 0.687, which is not as good as ours (AUC = 0.718 for 5‐year survival). 28 These studies including ours all suggested that LNM‐related genes were promising for many types of cancer in the prediction of overall survival.…”
Section: Discussionmentioning
confidence: 71%